1995
DOI: 10.7326/0003-4819-123-10-199511150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control, Proteinuria, and the Progression of Renal Disease

Abstract: Our study supports the concept that proteinuria is an independent risk factor for the progression of renal disease. For patients with proteinuria of more than 1 g/d, we suggest a target blood pressure of less than 92 mm Hg (125/75 mm Hg). For patients with proteinuria of 0.25 to 1.0 g/d, a target mean arterial pressure of less than 98 mm Hg (about 130/80 mm Hg) may be advisable. The extent to which lowering blood pressure reduces proteinuria may be a measure of the effectiveness of this therapy in slowing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
671
5
48

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,220 publications
(759 citation statements)
references
References 0 publications
30
671
5
48
Order By: Relevance
“…As for the optimal blood pressure (BP) in CKD patients, the recommended target systolic BP (SBP)/diastolic BP (DBP) is \140/90 mmHg for those without albuminuria and \130/80 mmHg for those with urine albumin excretion rates [30 mg/24 h, according to the Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guidelines [3]. The recommendations were derived from previous data such as those from the MDRD (Modification of Diet in Renal Disease) study and the AASK (AfricanAmerican Study of Kidney Disease and Hypertension), which demonstrated that aggressive BP control to lower BP targets was associated with a lower risk of CKD progression, especially in patients with proteinuria [4,5]. However, the lower limit of the optimal BP target range for patients with CKD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As for the optimal blood pressure (BP) in CKD patients, the recommended target systolic BP (SBP)/diastolic BP (DBP) is \140/90 mmHg for those without albuminuria and \130/80 mmHg for those with urine albumin excretion rates [30 mg/24 h, according to the Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guidelines [3]. The recommendations were derived from previous data such as those from the MDRD (Modification of Diet in Renal Disease) study and the AASK (AfricanAmerican Study of Kidney Disease and Hypertension), which demonstrated that aggressive BP control to lower BP targets was associated with a lower risk of CKD progression, especially in patients with proteinuria [4,5]. However, the lower limit of the optimal BP target range for patients with CKD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure (BP) level is widely recognized to strongly correlate with CKD, as it does with other cardiovascular diseases. [3][4][5] Clinical guidelines recommend using mean BP, systolic BP (SBP) and diastolic BP (DBP) for diagnosis and management of hypertension to prevent cardiovascular events such as progression of renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Nor should they diminish our enthusiasm for controlling hypertension in patients with primary renal disease, particularly those with proteinuria, where hypertension control has clearly been shown to attenuate the rate of progression to end-stage renal disease. 54, 55 The results of this metaanalysis however should encourage rethinking of whether non-malignant hypertension by itself is an important cause of renal dysfunction since the current best available data from randomised clinical trials fail to show that antihypertensive drug therapy reduces the incidence of renal dysfunction in patients with non-malignant hypertension.…”
Section: Discussionmentioning
confidence: 99%